1998
DOI: 10.1086/300449
|View full text |Cite
|
Sign up to set email alerts
|

The Hot Stars of Old Open Clusters: M67, NGC 188, and NGC 6791

Abstract: We analyze ultraviolet (∼ 1500Å) images of the old open clusters M67, NGC 188, and NGC 6791 obtained with Ultraviolet Imaging Telescope (UIT) during the second flight of the Astro observatory in March 1995. Twenty stars are detected on the UIT image of M67, including 11 blue stragglers, seven white dwarf candidates, and the yellow giant -white dwarf binary S1040. The ultraviolet photometry of the blue stragglers F90 (S975) and F131 (S1082) suggests that these stars have hot subluminous companions. We present a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(115 citation statements)
references
References 74 publications
8
106
1
Order By: Relevance
“…It is considered to be a BSS based on its location in the CMD. Landsman et al(1998) mentioned that this may have a composite spectrum, as suggested by its colors, with a possibility of a very hot star and a BSS as components. Siegel et al (2014) suspected this to be a red giant and a pre-WD binary.…”
Section: Uvit Datamentioning
confidence: 99%
See 2 more Smart Citations
“…It is considered to be a BSS based on its location in the CMD. Landsman et al(1998) mentioned that this may have a composite spectrum, as suggested by its colors, with a possibility of a very hot star and a BSS as components. Siegel et al (2014) suspected this to be a red giant and a pre-WD binary.…”
Section: Uvit Datamentioning
confidence: 99%
“…A total of 24 BSS candidates were cataloged by Ahumada & Lapasset (2007), with Geller et al (2008) showing 20 BSSs to be confirmed members based on their radial velocities. In their UIT study, Landsman et al (1998) identified three stars with exceptionally blue colors.…”
Section: Arxiv:161202535v1 [Astro-phsr] 8 Dec 2016mentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the figure shows fluxes in the FUV from all the filters, and fluxes in the NUV only from two filters. These flux distributions can be used to compare with models to estimate the temperature, mass and radius of the source, which is known to be a single lined binary (Geller et al 2008), with a suspected hot companion (Landsman et al 1998). b) The globular cluster, NGC 1851 has many UV-bright stars in its core and has been observed by Galex.…”
Section: Some Resultsmentioning
confidence: 99%
“…Evidence in favor of the high-metallicity scenario is provided by the presence of EHB stars in high-Z open clusters, including the ∼ 7 Gyr-old ( [81]) NGC 188 ( [48]) and the ∼ 8 Gyr-old ( [12]) NGC 6791 ( [46,45,48,9,12,33]). Both of these clusters are well known for their supersolar metallicities (e.g., [89]).…”
Section: Introductionmentioning
confidence: 99%